Efektivitas Teknik Komunikasi Asertif dalam Konseling Lintas Budaya pada Konflik Pertemanan Mahasiswa - Siti Aisyah; Fadhilla Yusri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to examine the effectiveness of assertive communication techniques in cross-cultural counseling for reducing avoidance behavior among students experiencing interpersonal friendship conflicts. Cultural differences between counselors and clients may influence communication patterns, emotional expression, and conflict resolution processes during counseling sessions. Friendship conflicts among university students commonly arise from jealousy, misunderstanding, social comparison, and ineffective interpersonal communication. These conditions often encourage students to avoid direct interaction to prevent further conflict. This study employed an experimental method using a One Group Pretest-Posttest Design. The participants were students who experienced friendship conflicts and demonstrated avoidance behavior tendencies. Data were collected through counseling individual. The intervention was delivered through counseling sessions that used assertive communication techniques and combined behavioral and humanistic approaches in a cross-cultural counseling setting. The findings revealed that assertive communication techniques were effective in reducing students’ avoidance behavior. After receiving the intervention, participants demonstrated greater confidence in expressing opinions, improved emotional regulation, increased openness in communication, and healthier interpersonal relationships. The study indicates that assertive communication in cross-cultural counseling can serve as an effective counseling strategy to help students manage interpersonal conflicts and improve social adjustment in higher education environments.